2023
DOI: 10.1172/jci.insight.164296
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the metabolic reprogramming induced by sodium-glucose cotransporter 2 inhibition

Abstract: Diabetes is associated with increased risk for kidney and liver diseases, congestive heart failure, and mortality. Urinary glucose excretion using sodiumglucose cotransporter 2 (SGLT2) inhibitors prevents these adverse outcomes, however the mechanisms involved are not clear. Herein, we generated a roadmap of the metabolic alterations that occur in the kidney, liver, and heart in diabetes and in response to SGLT2 inhibition. We performed in vivo metabolic labeling with 13 C-glucose in normoglycemic and diabetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 48 publications
0
6
0
2
Order By: Relevance
“…Our findings are consistent with prior studies that showed reduced glycolysis in diabetes (23, 31). In addition, a mouse study elucidated the impaired glycolysis in diabetic mice by labeling with 13 C-glucose characterized by increased glucose influx in diabetic mice (25). However, in this study, SGLT2i failed to reverse the dysfunction, which may be due to insufficient duration of treatment with SGLT2i.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings are consistent with prior studies that showed reduced glycolysis in diabetes (23, 31). In addition, a mouse study elucidated the impaired glycolysis in diabetic mice by labeling with 13 C-glucose characterized by increased glucose influx in diabetic mice (25). However, in this study, SGLT2i failed to reverse the dysfunction, which may be due to insufficient duration of treatment with SGLT2i.…”
Section: Discussionmentioning
confidence: 99%
“…However, in another mouse model of type 1 diabetes, treatment with an SGLT2i failed to rescue glycolysis. SGLT2 inhibition increases glucose oxidation in multiple organs (25). Thus, the role of SGLT2i in glycolysis is still under debate.…”
Section: Introductionmentioning
confidence: 99%
“…SGLT2i reduce glucose load by increasing glycosuria, thereby causing changes in glucose metabolism. SGLT2i inhibit hepatic glycolysis by inhibiting pyruvate kinase [ 76 ]. Animal experiments have also demonstrated that the down-regulation of Phosphoenolpyruvate carboxykinase (PEPCK) and Glucose-6-phosphatase (G6Pase) activities by Adenosine 5 ‘-monophosphate (AMP)-activated protein kinase/ cAMP-response element binding protein (AMPK/CREB) signaling pathway can inhibit hepatic gluconeogenesis, and the activation of AMPK/ Glycogen synthase kinase 3β (GSK3β) signaling pathway in vivo can promote glycogen synthesis [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among these pathways, the most extensively studied is the activation of the mTOR signaling pathway by leucine [ 26 , 35 ]. mTOR, a serine–threonine protein kinase, is a member of the PI3K-related kinase (PIKK) family and functions as the catalytic component for two separate complexes known as mTORC1 and mTORC2 [ 36 , 37 , 38 ]. Besides controlling the production of proteins by overseeing the messenger ribonucleic acid (mRNA) translation process, the intracellular mTOR molecule serves as a critical regulator in various essential cellular processes, including cell growth, cell division, autophagy, and glucose balance [ 39 ].…”
Section: Branched-chain Amino Acid-regulated Signaling Pathwaysmentioning
confidence: 99%
“…The majority of the energy is normally produced through fatty acid oxidation in the mitochondria, with a return to the fetal pattern of cardiac development in a pathological state, in which anaerobic glycolytic metabolism, with its high use of ketones and lactate and a decrease in fatty acid use, is characteristic [ 50 , 55 ]. This alternative adaptive mechanism is only beneficial in the short-term, extended use of glucose, causing a deficiency in ATP production commonly observed in various cardiac diseases [ 37 , 56 , 57 , 58 ]. ATP generation through the tricarboxylic acid (TCA) cycle in the mitochondria after fatty acid breakdown, together with the electrons generated and transferred through the electron transport chain (ETC), leads to the creation of a proton gradient and energy production [ 50 , 59 , 60 ].…”
Section: Branched-chain Amino Acid In Cardiovascular Diseasementioning
confidence: 99%